2014
DOI: 10.15789/1563-0625-2012-1-2-33-42
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of TNF-Binding Variolavirus Recombinant Protein

Abstract: Резюме. В настоящем обзоре собственных экспериментальных данныъх приведены результаты изучения in vivo и in vitro эффектов TNF-связывающего белка вируса натуральной оспы (VARV-CrmB) на TNF-зависимые изменения функциональной активности мышиных и человеческих клеток. In vitro VARV-CrmB отменяет вызываемую TNF повышенную продукцию IL-1β и IL-6 мононуклеарными клетками человека и их повышенную окислительно-метаболическую активность. Рекомбинантный белок VARV-CrmB восстанавливает TNF-индуцированное снижение количес… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Complete or partial remission was achieved in less than half of patients, and approxi mately one third of patients have to cease treatment because of the development of secondary inefficiency or side effects [3]. In particular, this may be due to development of an immune response to the repeatedly administered protein (the size of the above mentioned TNF antagonists is 148-150 kDa) [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complete or partial remission was achieved in less than half of patients, and approxi mately one third of patients have to cease treatment because of the development of secondary inefficiency or side effects [3]. In particular, this may be due to development of an immune response to the repeatedly administered protein (the size of the above mentioned TNF antagonists is 148-150 kDa) [4].…”
mentioning
confidence: 99%
“…The recombinant full length VARV CrmB was synthesized in eukaryotic baculovirus system. Its high efficiency as a TNF antagonist was demonstrated in various laboratory models both in vitro and in vivo [3,6]. It was found that the viral TNF binding protein VARV CrmB is a two domain protein and, along with TNF, binds to a number of chemokines [7].…”
mentioning
confidence: 99%